Îngrijind copiii instituţionalizaţi: percepţia personalului din apartamentele de tip familial din Bucureşti asupra muncii lor - Lipan, Ştefan (Calitatea Vieții, 2017)
An important aspect of Romania’s modernization project was the restructuring of the childcare system. The large institutions were closed and new, small sized ones, were created. One example are the ones called „family type apartments”, where three to eight children live. Moreover, a new regulation based on the enforcement of quality standards and licensing was introduced. This research tries to bring a clearer picture of the effects these shifts have had, having as a point of departure the way the people employed in family type apartments envision their work. They are the ones who spent the most time with the children and the ones who have a major influence in their development. They consider their work to be made up of many different roles, some of them unclear, for which they are held responsible, even though for some of them, they don’t have the proper qualifications. Administrative and bureaucratic activities are seen as occupying too much of their work time, time which could be better spent with educational activities. They also invest a lot of energy in the “emotional labour” they carry out with children. This can lead to exhaustion and can have harmful effects for the relationship they have with children. This article suggests that the restructuring projects introduced so far have not sufficiently taken in consideration employees perspectives and needs, and those of children themselves.